Pertumbuhan, Hasil dan Translokasi Timbal (Pb) pada Tanaman Kangkung (Ipomea reptans) dan Bayam (Amaranthus tricolor L.) Dengan Penambahan Pupuk ZA Berbeda Dosis - Rubiatul Adawiyah; Anis Rosyidah (Folium : Jurnal Ilmu Pertanian, 2020)
Lead (Pb) is the heavy metal that causes the most pollution in the environment. This study was conducted to compare the ability of water spinach and spinach plants to absorb lead due to the administration of various doses of ZA as a heavy metal suppressor on polluted land. This research is a pot experiment using a factorial randomized block design (RBD) with two factors. The first factor is the type of plant (Kangkung and Spinach). The second factor was the dose of ZA fertilizer  (0; 1.19; 2.38 3.57; 4.76 g / pot). The variables observed included growth, plant yield, and Pb concentration in plants. The results showed that the growth of kale plants increased with the increasing dose of ZA application up to 2.38 g / pot. Increasing the dose gave an insignificant increase in growth (P <0.05), likewise in spinach plants. However, higher doses caused a significant reduction in the number of spinach leaves (P <0.05). The fresh weight of kale roots and shoots significantly increased by an average of 50.74% and 36.57% compared to the control. While the spinach plant experienced an increase in the average root and shoot fresh weight significantly by 50.76% and 53.10% compared to the control. Water spinach plants accumulated more Pb in the crown with an average Translocation Factor (TF) value of 1.09. Meanwhile, spinach plants accumulated more Pb in their roots with an average TF value of 0.75. These results suggest that the application of ZA increases the Pb uptake of plant hyperaccumulators from vegetables. However, spinach is safer to eat because heavy metals are accumulated in the roots. Keywords: Phyitoremediation, Lead, water spinach, spinach, ZA, Translocation.